Iowa RBA, December 22, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Email of the Iowa RBA update for December 22, 1997. Highlights of the update include observations of several outstanding birds from seven Christmas Bird Counts held around the state. The best birds discovered on the counts were several species of Gulls and Woodpeckers as well as White-winged Crossbills, Long-tailed Ducks, and Common Redpolls. Also included are handwritten notes for the next week's update with sightings of Ruby-crowned Kinglet, Merlin, and Surf Scoter. Epson - sheet feed/flatbed